Undersea muon detectors monitor variations in water depth. (1st August 2022) - Jarman, Sam
Abstract : An international team of researchers has installed an array of undersea muon detectors that can monitor variations in water depth. The system measured how a distant typhoon caused the water level in Tokyo Bay to oscillate over timescales of several hours.